Internet financial reporting dan asimetri informasi: Apakah berdampak pada nilai perusahaan? - Agnes Susana Soenjoyo; Lindrawati Lindrawati (Jurnal Manajemen Maranatha, 2025)
Investors, in making decisions, look at the firm value where information sources are increasingly easily accessible and transparent in the form of internet financial reporting on the company website, as well as the information asymmetry that occurs. This research analyzes the impact of internet financial reporting and information asymmetry on firm value. Quantitative research design with data sources from annual reports and stock prices. The research objects are financial sector companies on the Indonesia Stock Exchange which have active websites. Data analysis technique uses multiple linear regression analysis. The research results show that internet financial reporting positively impacts firm value, while information asymmetry does not. When there are additional features, updates, and wider disclosure of information on company websites, they can help investors obtain information more easily and quickly about the company’s condition, thereby increasing firm value. Therefore, regulations regarding internet financial reporting need to be improved.